2017
DOI: 10.3390/mti1030017
|View full text |Cite
|
Sign up to set email alerts
|

A State-of-the-Art Review of Augmented Reality in Engineering Analysis and Simulation

Abstract: Augmented reality (AR) has recently become a worldwide research topic. AR technology renders intuitive computer-generated contents on users' physical surroundings. To improve process efficiency and productivity, researchers and developers have paid increasing attention to AR applications in engineering analysis and simulation. The integration of AR with numerical simulation, such as the finite element method, provides a cognitive and scientific way for users to analyze practical problems. By incorporating scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 82 publications
0
68
0
7
Order By: Relevance
“…[18] proposes the use of a 3D holographic system using a real size virtual replica, and by using mobile devices integrated into the factory and in the classroom, while Centea [19] implements a dual education system collaboration between industry and university to train students and employees involving TF. Another tendency is the use of mixed reality in learning about factories as suggested in [20], displaying information about on-site working environments [21]. The problem for the MR use is when no equipment exists or the training needs to be implemented in safety situations without risking trainers and equipment [22], such as the presented case.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] proposes the use of a 3D holographic system using a real size virtual replica, and by using mobile devices integrated into the factory and in the classroom, while Centea [19] implements a dual education system collaboration between industry and university to train students and employees involving TF. Another tendency is the use of mixed reality in learning about factories as suggested in [20], displaying information about on-site working environments [21]. The problem for the MR use is when no equipment exists or the training needs to be implemented in safety situations without risking trainers and equipment [22], such as the presented case.…”
Section: Related Workmentioning
confidence: 99%
“…The evaluations consider the job skills that the student will need in the industry; from the selection of equipment, design of photovoltaic arrangements, calculations of conductor sizes and protection devices, the use of personal protective equipment, and the amount of power generation taking into account the value of 5 hrs of solar radiation typically used in the literature. 20 Determine the capacity of the DC and AC switches 7…”
Section: Academic Contextmentioning
confidence: 99%
“…In the field of Teaching and learning, markers in the form of images on the pages of books, tables of chemical elements, or attached to learning media that cause the size of the digital object displayed to adjust the place [2][3][4][5][6][7][8][9][10][11]. In the field of Product and Marketing, customers usually immediately try to use the product and want to get more interactive information [12][13][14][15][16][17][18][19][20][21]. The illustration of marker weaknesses from the previous research is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been considerable interests in interpreting building design in virtual environments, investigations on visualizing the performance simulation together in AR/MR are still insufficient. Interrogatively visualizing these data in the AR/MR can decrease misinterpretations and help designers make correct decisions (Li et al 2017). This topic was firstly coined by Belcher & Johnson (2008a) who superimposed the virtual model with light simulation data obtained from software Radiance and Ecotect.…”
Section: Introductionmentioning
confidence: 99%